2023
DOI: 10.3389/fimmu.2023.1128301
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy: A promising novel endometriosis therapy

Abstract: Endometriosis is a common disease of the female reproductive system and has malignant features. Although endometriosis by itself is a benign disease, its erosive growth characteristics lead to severe pelvic pain and female infertility. Unfortunately, several aspects of the pathogenesis of endometriosis are still unclear. Furthermore, the clinical therapeutic methods are unsatisfactory. The recurrence rate of endometriosis is high. Accumulating evidence suggests that the onset and development of endometriosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 95 publications
1
4
0
Order By: Relevance
“…In this study, the distribution of most immune cells was dysregulated in EMs, which is consistent with the findings of previous studies ( 14 , 32 ). In particular, EMs was associated with decreased cytotoxicity of NK cells, an increased abundance and cytotoxicity of macrophages, aberrant activation of T cells and B cells, and enhanced density and number of mast cells and dendritic cells.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the distribution of most immune cells was dysregulated in EMs, which is consistent with the findings of previous studies ( 14 , 32 ). In particular, EMs was associated with decreased cytotoxicity of NK cells, an increased abundance and cytotoxicity of macrophages, aberrant activation of T cells and B cells, and enhanced density and number of mast cells and dendritic cells.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, immune therapy holds promise as a potential treatment approach for this condition. The reduced macrophagic phagocytosis observed in the serum and peritoneal fluid of individuals with endometriosis is a significant contributor to the disruption of immune balance[ 262 ]. In this sense, the expression of CD47 is used by macrophages to distinguish “self” or “non-self” cells.…”
Section: Implications For Clinical Managementmentioning
confidence: 99%
“…Furthermore, it has been reported that exosomes originating from endometriosis can induce a shift in macrophage phenotype toward M2 polarization, leading to a reduction in macrophage phagocytic activity both in laboratory settings ( in vitro ) and within the body ( in vivo )[ 262 ]. As a result, employing anti-exocrine therapy for individuals with endometriosis appears to have a notable effect on attracting macrophages to ectopic lesions[ 266 ].…”
Section: Implications For Clinical Managementmentioning
confidence: 99%
“…The study of autoantibodies to molecules that play an important role in the pathophysiology of endometriosis, in particular to specific endometrial antigens (TPM, TMOD), the glycolytic enzyme α-enolase 1 (ENO) involved in endometrial cell invasion, as well as to steroids (estradiol (E2), progesterone (PG)) and gonadotropins, in various forms of endometriosis, may contribute to a deeper understanding of the immune aspects of the pathophysiology of endometriosis, identifying promising diagnostic biomarkers and proposing new treatment strategies [23]. In connection with the above, the aim of this study was to evaluate the profile of serum autoantibodies and their diagnostic and pathogenetic significance in ovarian endometrioma and deep infiltrative endometriosis.…”
Section: Introductionmentioning
confidence: 99%